Ovarian Seromucinous Borderline Tumor and Clear Cell Carcinoma: An Unusual Combination - Eriko Nakamura; Yuichiro Sato; Sayaka Moriguchi; Atsushi Yamashita; Takashi Higo; Yujiro Asada (Case Reports in Obstetrics and Gynecology)
Ovarian seromucinous borderline tumors (SMBTs) are rare. They architecturally resemble serous borderline tumors but are much more frequently associated with endometriosis. The coexistence of other tumors with seromucinous tumors is also extremely rare. Here, we report an unusual combination of bilateral ovarian SMBT and clear cell carcinoma associated with polypoid endometriosis of the colon, in a 62-year-old woman. There was no transitional lesion between the two tumors. Immunohistochemistry showed different staining patterns in tumor components. Seromucinous tumor cells were positive for estrogen receptor (ER) and progesterone receptor (PgR) but negative for Napsin A, p504S, and HNF1B. Clear cell tumor cells were positive for Napsin A and p504S and focally positive for HNF1B but negative for ER and PgR. Loss of ARID1A expression was not observed in SMBTs, clear cell tumors, or endometriosis. These findings suggest that these tumors arose from separate endometriosis foci and collided within the same ovary. To the best of our knowledge, this is the first case of this unusual combination of ovarian seromucinous tumor and clear cell carcinoma to be reported in the English literature.